Spreading Gangs: Exporting US Criminal Capital to El Salvador - Sviatschi, Maria Micaela (American Economic Review, 2022)
This paper shows how deportation policies can backfire by disseminating not only ideas between countries but also criminal networks, spreading gangs, in this case, across El Salvador, and spurring migration back to the United States. In 1996, the US Illegal Immigration Responsibility Act increased the number of criminal deportations. In particular, the members of large Salvadoran gangs developed in Los Angeles were sent back to El Salvador. Using variation in criminal deportations over time and across cohorts, combined with geographical variation in US gangs’ location, I find that these deportations led to an increase in homicide rates and gang activity, as well as an increase in gang recruitment and migration of children. (JEL J15, J18, K37, K42, O17)